“Superfluous Men” in Russian Literature: Gogol’s View - Igor’ A. Vinogradov (Studia Litterarum)
Among the hitherto understudied “key” concerns of Gogol’s work is the author’s attitude to the types of the so-called “superfluous men.” This essay analyzing a number of Gogol’s fictional and essayistic works, for the first times delineates his typology of the “grieving man” — a literary contemporary of “superfluous men” represented by Onegin and Pechorin as well as other characters by M.Yu. Lermontov, N.G. Chernyshevsky, F.M. Dostoevsky, A.I. Herzen, N.A. Nekrasov, I.S. Turgenev and others. The essay offers a new historical and literary context and techniques of close reading to the study of this canonical theme that has been routinely included as a student’s paper topic in the class. The long-established routine of studying the “superfluous man” stems from the well-known statement of V.G. Belinsky about Eugene Onegin as a “selfish willy-nilly” — a man allegedly limited in his personal development due to the lack of professional realization of his potential. According to Gogol, the problem is rooted not in the imperfections of the political system but in the need for spiritual and professional growth of “ignoramuses,” representatives of his gallery of the numerous “dead souls.”